Protocol for quantitative evaluation of the impact of paracrine senescence on cellular reprogramming in cultured cells and mouse models - Jérémy Chantrel; Cheng Chen; Jun Zhang; Han Li (STAR Protocols, 2023)
Summary: We present a protocol to evaluate the impact of senescence secretome on reprogramming to pluripotency using both cellular and mouse models. First, we describe the in vitro reprogramming procedure using conditioned medium derived from senescent cells. Next, to explore the impact of senescence on in vivo reprogramming, we detail the steps to identify senescent and reprogrammed cells in mouse skeletal muscle, followed by semi-automatic quantification. This protocol can be used to study the effect of paracrine senescence on cellular plasticity.For complete details on the use and execution of this protocol, please refer to von Joest et al. (2022).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.